2017
DOI: 10.1080/10245332.2017.1375064
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the HLA-A/B/DRB1 polymorphisms and aplastic anemia: evidence from 17 case–control studies

Abstract: In conclusion, HLA-A/B/DRB1 polymorphisms may play an important role in AA, but higher quality and larger sample studies are needed to confirm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…Aplastic anemia is associated with specific histocompatibility antigens 2627 . More striking is the presence of “escape clones”, granulocytes with loss of the region of chromosome 6 that encompasses HLA alleles, in 10–15% of patients 2829,30 ; cells selected by absence of HLA, acquired by 6pLOH or somatic mutations, sustain hematopoiesis by clonal expansion 31 Immune escape has been hypothesized to explain clonal expansion of cells globally deficient in glycosylphosphoinositiol (GPI)-anchored proteins 32 in PNH, due to an acquired mutation in PIG-A in a stem cell.…”
Section: Pathophysiologiesmentioning
confidence: 99%
“…Aplastic anemia is associated with specific histocompatibility antigens 2627 . More striking is the presence of “escape clones”, granulocytes with loss of the region of chromosome 6 that encompasses HLA alleles, in 10–15% of patients 2829,30 ; cells selected by absence of HLA, acquired by 6pLOH or somatic mutations, sustain hematopoiesis by clonal expansion 31 Immune escape has been hypothesized to explain clonal expansion of cells globally deficient in glycosylphosphoinositiol (GPI)-anchored proteins 32 in PNH, due to an acquired mutation in PIG-A in a stem cell.…”
Section: Pathophysiologiesmentioning
confidence: 99%
“…AA development has also been associated with specific human leukocyte antigens (HLA) 82 . Class I HLA molecules, such as HLA A02:01, A02:06, A31:01, and B4:02, can act as auto-antigens and are targeted by cytotoxic T cells 83 .…”
Section: Clonalitymentioning
confidence: 99%
“…6pLOH(+) clones have been detected in 11%-13% of AA patients. Reduced HLA auto-antigen expression gives stem cells an opportunity for clonal outgrowth as an "escape" from the autoimmune attack [82][83][84][85][86] . This may be the mechanism by which hematopoiesis is maintained for years in AA patients 83 .…”
Section: Clonalitymentioning
confidence: 99%
“…Babushok et al identified somatic mutation in HLA class I genes including 4 HLA alleles; HLA-A*33.03, HLA-A*68.01, HLA-B*14:02, and HLA-B*40:02, related to more severe disease and predisposing to other chromosomal abnormalities and clonal changes, thus supporting the link between inherited abnormalities and clonal evolution in the course of AA [32]. Also, HLA class II gene related autoimmunity has been revealed [2,[32][33][34][35][36][37]. Comparing AA and hypoplastic MDS patients, including MDS secondary to AA, using SNP array-based karyotyping, Afable et al reported lesions involving the HLA locus suggestive of clonal immune escape in some AA patients [38].…”
Section: Clonal Haematopoiesis Of Hematopoietic Stem Cellmentioning
confidence: 89%